#FamilyisLove: understanding extreme life experiences and psychological profile of pre-service teachers in the Philippines - Dechavez, January (Frontiers in Public Health, 2024)
Despite the focus of studies in other countries that emphasize the significant impact of household and school experiences on child development, in the Philippines, the few studies available tend to focus on the prevalence of suicide cases, bullying, and other school experiences that impact mental health. No explicit studies relate demographic information, relationships and past experiences, personality variables, and household treatment among Filipino students with regard to their own mental wellbeing. Thus, with the primary aim of describing the psychological profile of second-year pre-service teachers taking Bachelor of Technical Vocational Teacher Education for the academic year 2019–20 and to identify possible interventions and propose policy recommendations to promote mental healthcare, wellbeing, and resilience, the Basic Personality Inventory (BPI) results and focus group discussion interview texts were utilized for this investigation. The explanatory sequential mixed methods research was employed to undertake a study of student participants (n = 91) aged 18–35 years (X̄ = 19.9 years, SD = 2.00) using descriptive statistical tools for quantitative data derived from BPI results and textual/thematic analysis (visual and content) for qualitative data. The dominant personality variables reported as areas of weakness were thinking disorder, persecutory ideas, deviation, and self-depreciation. On the other hand, the identified areas of strength were cooperativeness, capacity for self-criticism, cheerfulness, and socially responsible attitudes. Finally, familial relationships/household treatment and previous experiences at home and in school contributed to the respondents’ strengths and weaknesses. For this reason, various mental health-related intervention activities, policies, and programs are recommended.